Revision of the West Palaearctic Euura bergmanni and oligospila groups (Hymenoptera, Tenthredinidae) - Marko Prous; Andrew Liston; Marko Mutanen (Journal of Hymenoptera Research, 2021)
Eight Western Palaearctic Euura species are here assigned to the bergmanni group (bergmanni, brevivalvis, dispar, glutinosae, leptocephalus, respondens, sylvestris, and viridis) and two species to the oligospila group (frenalis and oligospila). Euura pallens (Konow, 1903) (bergmanni group) is removed from the list of West Palaearctic taxa. Euura pyramidalis (Hellén, 1948) is treated as incertae sedis within the bergmanni group. Definitions of the bergmanni and oligospila groups are primarily based on genetic sequence data (mitochondrial COI and nuclear NaK and POL2). We report likely occurrence of heteroplasmy and amplification of NUMTs among some of the treated species, complicating the use of DNA barcoding in species discrimination. Based on morphological and genetic evidence, we establish that the correct name for the invasive willow sawfly in the southern hemisphere (South America, southern Africa, Australia, New Zealand), known there only in the female sex, is Euura respondens (Förster, 1854). The species is probably native to the Palaearctic (or even Holarctic) where males are common: possibly as common as females (examined from Europe and Central Asia). The name Euura oligospila (Förster, 1854) has been incorrectly used for the species in the southern hemisphere. The examination of type material and reliable association of males and females based on genetics revealed that females of E. oligospila are morphologically extremely similar to E. respondens (and to some other E. bergmanni group species), but male penis valves and genetics enable reliable separation of these species. Morphological separation of females of E. oligospila and E. respondens is possible, but challenging. Identification keys for males and females of the bergmanni and oligospila groups are provided. The following 15 new synonymies are proposed: Nematus validicornis Förster, 1854, syn. nov. with Euura bergmanni (Dahlbom, 1835); Pteronidea woollatti Lindqvist, 1971, syn. nov. and Nematus turgaiensis Safjanov, 1977, syn. nov. with Euura brevivalvis (Thomson, 1871); Pteronidea pseudodispar Lindqvist, 1969, syn. nov. with Euura dispar (Zaddach, 1876); Nematus (Pteronidea) fastosus var. ponojense Hellén, 1948, syn. nov. and N. (P.) fastosus var. punctiscuta Hellén, 1948, syn. nov. with Euura frenalis (Thomson, 1888); Nematus declaratus Muche, 1974, syn. nov. and N. desantisi D.R. Smith, 1983, syn. nov. with Euura respondens (Förster, 1854); Pteronidea straminea Lindqvist, 1958, syn. nov., P. angustiserra Lindqvist, 1969, syn. nov., and P. disparoides Lindqvist, 1969, syn. nov. with Euura sylvestris (Cameron, 1884); Pteronidea breviseta Lindqvist, 1946, syn. nov., P. breviseta Lindqvist, 1949, syn. nov., P. abscondita Lindqvist, 1949, syn. nov., and P. lauroi Lindqvist, 1960, syn. nov. with Euura viridis (Stephens, 1835). Lectotypes are designated for 18 nominal taxa: Amauronematus longicornis Konow, 1897; A. spurcus Konow, 1904; Nematus bergmanni Dahlbom, 1835; N. brevivalvis Thomson, 1871; N. curtispina Thomson, 1871; N. (Pteronidea) fastosus var. ponojense Hellén, 1948; N. (P.) fastosus var. punctiscuta Hellén, 1948; N. glutinosae Cameron, 1882; N. microcercus Thomson, 1871; N. polyspilus Förster, 1854; N. prasinus Hartig, 1837; N. respondens Förster, 1854; N. salicivorus Cameron, 1882; N. validicornis Förster, 1854; N. virescens Hartig, 1837; Pteronidea curtispina var. luctuosa Enslin, 1916; Pteronus fastosus Konow, 1904; and P. pallens Konow, 1903.